A systems review of grain proteins in rice and barley: biosynthesis, regulation, and impact on end-use quality - ElShamey, Essam; Yang, Xiaomeng; Yang, Jiazhen; Xia, Li; Zeng, Yawen (Frontiers in Plant Science, 2025)
Grain proteins in cereal crops play a crucial role in determining both the nutritional value and end-use quality of food products. This systematic review comprehensively examines the biosynthetic pathways, regulatory mechanisms, and functional impacts of storage proteins in rice (Oryza sativa) and barley (Hordeum vulgare), two of the world’s most important staple crops. Rice and barley are significant sources of bioactive proteins, which are fundamental to their nutritional value and health promoting properties. The major storage proteins, including glutelins, prolamins (with hordeins being the major type in barley), and globulins, are synthesized under the regulation of key transcription factors like RISBZ and RPBF in rice and BLZ1/2 in barley. These proteins provide essential amino acids and are a source of bioactive peptides with demonstrated anti-hypertensive, immunomodulatory, and cholesterol-lowering activities. Furthermore, the review considers the influence of genetic and environmental factors on protein profiles. The health implications of rice and barley proteins are discussed, underscoring their potential in functional foods and nutraceuticals. Future perspectives highlight the promise of metabolic engineering and precision breeding for the biofortification and nutritional enhancement of these vital cereals.